Influence of residual stresses on the fatigue life of welded joints. Numerical simulation and experimental tests. (September 2022) - Chiocca, Andrea; Frendo, Francesco; Aiello, Francesco; Bertini, Leonardo
Abstract: Residual stresses constitute an inevitable consequence of the most ordinary manufacturing processes, leading to high and not easily foreseeable stress field within a component. Fatigue design codes typically address residual stresses by means of very conservative assumptions, which may results in poorly optimized designs and unexpected failures. Nowadays, the increasing motivation towards an optimized material application require a more reliable fatigue assessment of welded joints and residual stress evaluation. This study investigates the influence of residual stresses on the fatigue assessment of a S355JR structural steel pipe-to-plate welded joint subjected to fully-reversed torsional and bending loading. Influencing factors, such as geometric discontinuities and the material heterogeneous microstructure were considered through numerical modelling and microstructural analysis respectively. Firstly, an uncoupled thermal–structural finite element simulation was carried out to assess the complete residual stress field within the specimen generated by a gas metal arc welding process. Both thermal and structural simulations were developed to achieve an optimal trade-off between simulation time and results accuracy. Then, residual stresses were mapped and included as initial condition in numerical models intended for fatigue damage factors calculation. Fatigue analysis was conducted by means of the Fatemi–Socie critical plane factor and the hydrostatic stress as local damage parameters. Experimental results were then used to corroborate numerical models and verify their capability in assessing the fatigue endurance. Both the experimental data and the applied damage factors have shown an effect of residual stresses on the fatigue life of welded joints when torsional loading was applied. Data further agreed that no influence of residual stresses was detected in the case of bending loading. Graphical abstract: Highlights: The fatigue strength of stress relieved and as-welded welded joints was studied. Experimental tests and FE analyses were used to study the effect of residual stresses. A dissimilar influence of residual stresses was observed under torsion and bending load. The hydrostatic stress component and the Fatemi–Socie critical plane factor succeeded in describing the different observed fatigue endurance.